Stem cell-derived retinal pigment epithelium from patients with age-related macular degeneration exhibit reduced metabolism and matrix interactions. (16th December 2019) - Gong, Jie; Cai, Hui; ,; Noggle, Scott; Paull, Daniel; Rizzolo, Lawrence J.; Del Priore, Lucian V.; Fields, Mark A.
Abstract: Modeling age-related macular degeneration (AMD) is challenging, because it is a multifactorial disease. To focus on interactions between the retinal pigment epithelium (RPE) and Bruch's membrane, we generated RPE from AMD patients and used an altered extracellular matrix (ECM) that models aged Bruch's membrane. Induced pluripotent stem cells (iPSCs) were generated from fibroblasts isolated from AMD patients or age-matched (normal) controls. RPE derived from iPSCs were analyzed by morphology, marker expression, transepithelial electrical resistance (TER), and phagocytosis of rod photoreceptor outer segments. Cell attachment and viability was tested on nitrite-modified ECM, a typical modification of aged Bruch's membrane. DNA microarrays with hierarchical clustering and analysis of mitochondrial function were used to elucidate possible mechanisms for the observed phenotypes. Differentiated RPE displayed cell-specific morphology and markers. The TER and phagocytic capacity were similar among iPSC-derived RPE cultures. However, distinct clusters were found for the transcriptomes of AMD and control iPSC-derived RPE. AMD-derived iPSC-RPE downregulated genes responsible for metabolic-related pathways and cell attachment. AMD-derived iPSC-RPE exhibited reduced mitochondrial respiration and ability to attach and survive on nitrite-modified ECM. Cells that did attach induced the expression of complement genes. Despite reprogramming, iPSC derived from AMD patients yielded RPE with a transcriptome that is distinct from that of age-matched controls. When challenged with an AMD-like modification of Bruch's membrane, AMD-derived iPSC-RPE activated the complement immune system. : Abstract : Bruch's membrane is the extracellular matrix (ECM) that underlies the retinal pigment epithelium (RPE). ECM cross-linked by nitrosylation is a typical attribute of aging. Using a model of aged Bruch's membrane, we demonstrate that iPSC-derived RPE from AMD patients are inherently less able to attach and survive on nitrosylated ECM compared to controls.